Taboo Language, Attention, and Branding: A Psycholinguistic Study of Timothy Ronald's Language Style on YouTube - Lintang Ikhsan; Eko Suroso (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
Foul speech is seen not solely as a negative emotional expression, but as a linguistic strategy that is able to attract attention, evoke emotions, and strengthen the creator's personal identity. Therefore, this study describes the relationship between coarse speech, audience attention, and personal branding in content creator Timothy Ronald's communication style on the YouTube platform through a psycholinguistic approach. The research method used was qualitative descriptive by analyzing speech data from Timothy Ronald's YouTube videos, complemented by observation of audience comments to identify social and emotional responses. The results of the study show that the form of coarse speech used by Timothy Ronald has a psycholinguistic function in the form of emotional, evaluative, conative, and persuasive expressions that have implications for the formation of self-image as a communicative figure who is straightforward, honest, and critical of social reality. Simultaneously, the use of harsh language with a high rhetorical level succeeded in creating a strong attention effect, provoking the emotional resonance of the audience, and strengthening personal branding as an authentic communicator in the digital space. Thus, this study confirms that coarse speech can play a role as an effective communication strategy that connects aspects of language, cognition, and emotion in shaping social influence and digital identity in the new media era.